2018
DOI: 10.1089/cyber.2017.0599
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Video Gaming in a Young Spanish Population: Association with Psychosocial Health

Abstract: Problematic video gaming (PVG) is a concern for psychologists attending children and adolescents. Uniform diagnostic criteria are lacking, and risk factors are poorly understood. Internet gaming disorder (IGD) was included in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5), and scales derived from its diagnostic criteria may be helpful to assess PVG. A multicenter study was conducted in secondary schools using an IGD-derived scale (dichotomous Nine-Item Internet Gaming Disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1
8

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 34 publications
3
23
1
8
Order By: Relevance
“…The prevalence rate of IGD in the present sample was 1.9%, which is similar to the 2.6% found in another Spanish sample by Fuster et al [37] but noticeably lower than that of 8.3% reported by Buiza-Aguado et al [36]. These discrepancies may be due to the use of different psychometric tools in assessing IGD.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The prevalence rate of IGD in the present sample was 1.9%, which is similar to the 2.6% found in another Spanish sample by Fuster et al [37] but noticeably lower than that of 8.3% reported by Buiza-Aguado et al [36]. These discrepancies may be due to the use of different psychometric tools in assessing IGD.…”
Section: Discussionsupporting
confidence: 72%
“…In Spain (where the present study was carried out), a study with a school sample of 708 students reported 72.8% online gamers [36] of whom 8.3% met five or more of the nine criteria for IGD (86.44% were male). Another study conducted with Spanish-speaking online gamers reported a prevalence of 2.6% disordered gamers [37].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…El 72,16% de nuestra muestra había jugado a videojuegos en el último mes, un porcentaje muy similar al reportado por jugadores jóvenes en España (Buiza-Aguado, Alonso-Canovas, Conde-Mateos, Buiza-Navarrete y Gentile, 2018). No obstante, el porcentaje de jugadores diarios era mucho más bajo (22,7%), otro resultado comparable con el de los adolescentes españoles (Gonzálvez, Espada y Tejeiro, 2016).…”
Section: Discussionunclassified